P5-PPRA: Langkah Strategis Membangun Generasi Religius dan Berkarakter - Umi Hanik Noviana; Titi Kadi; saipulhadi bahruddin (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This research is motivated by the implementation of the Pancasila-based student profile strengthening project, known as P5-PPRA, in schools (including elementary madrasas/MI) implementing the Merdeka curriculum. The implementation of P5-PPRA has various objectives, including the formation of religious character. This is due to the phenomenon of character deteriorating day by day. The purpose of this study is to determine how the implementation of P5-PPRA in shaping the religious character of students at the Ma'arif NU 003 Samarinda Elementary Madrasah (MI). The type of research used in this study is descriptive qualitative. Data collection techniques include observations of P5-PPRA activities, interviews with fourth-grade homeroom teachers, the principal, and students, and documentation of P5-PPRA activities. The data validity test used triangulation techniques and sources. The data process was carried out using several stages, namely data condensation, data presentation, and drawing conclusions. Based on the results of the study, the implementation of the P5-PPRA program at MI Ma'arif NU 003 Samarinda was full of the formation of religious character of students. This is illustrated by three P5-PPRA activities, namely (1) a visit to the Siratal Mustaqim mosque, this visit can form religious character values ​​such as adherence to the teachings adopted, complete faith, love of worship and ta'addub and tolerance. Then (2) the activity of making a ketupat frame, through this activity religious character is also formed in the form of patience, simplicity and gratitude, obedience to Islamic traditions and creativity (a reflection of dynamic and innovative/tatawwur). Finally (3) the Jepen Eroh dance activity which forms religious characters such as ukhuwah insaniah and discipline (istiqomah).